Study on the influencing factors and composing path of online healthcare community use: an empirical study based on fsQCA - Wang, Zhanyou; Han, Dongmei; Ma, Liang; Hao, Feifei (Frontiers in Psychology, 2025)
In recent years, online healthcare communities have been widely adopted in China. However, the influencing factors and configuration paths affecting their usage remain unclear. This study employs Fuzzy-set Qualitative Comparative Analysis (fsQCA) to empirically investigate the determinants and combinatorial pathways leading to the use of online healthcare communities. Based on a cross-sectional survey design, data were collected via an online questionnaire using a snowball sampling method, resulting in 287 valid responses from users with experience in online healthcare platforms. The study examines condition configurations from the perspectives of patients, doctors, and platforms, identifying six sufficient combinatorial paths that lead to usage. Among these, the combination of perceived usefulness × perceived ease of use × platform trust exhibits the highest raw coverage. The findings enhance understanding of the mechanisms driving online healthcare community adoption and offer practical insights for platform optimization, policy-making, and future research.